Project Gutenberg Compilation of Short Stories by Chekhov - Chekhov, Anton Pavlovich, 1860-1904; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2018)
"Project Gutenberg Compilation of Short Stories by Chekhov" by Chekhov is a collection of short stories likely written in the late 19th century. This compilation includes a wide array of tales highlighting the intricacies of human nature, often set against the backdrop of Russian society. The stories evoke themes of love, loss, and the complexities of relationships, showcasing the plight of various characters navigating their personal struggles. The beginning of "The Horse-Stealers," the first story in the collection, introduces the character Yergunov, a hospital assistant who finds himself lost in a snowstorm after borrowing a horse from his doctor. As he stumbles upon a suspicious tavern known for its association with local thieves, Yergunov encounters interesting yet dubious characters, including a known horse thief named Kalashnikov. The atmosphere thickens with intrigue as Yergunov grapples with his own moral compass amidst the seedy setting, leading to a series of encounters that explore themes of bravado, shame, and desire. This opening sets the tone for a deeper exploration of human behavior and societal norms prevalent throughout Chekhov's work. (This is an automatically generated summary.)
Release date is 2018-06-15
David Widger
Keywords: Russia -- Social life and customs -- Fiction; Chekhov, Anton Pavlovich, 1860-1904 -- Translations into English; Short stories, Russian -- Translations into English; Russian fiction -- Translations into English